Perioperative group and save testing are not routinely indicated for emergency laparoscopic appendicectomy and laparoscopic hernia repairs: A North West London retrospective study. Issue 5 (May 2023) - Al-Musawi, Jasim; Reece, Ieuan; Chen, Jun Yu; Britton, Clemency; Shakweh, Ealaff; Vutipongsatorn, Kritchai; Ng, Clarissa; Kotecha, Shreeya; Lawler, Michael; Daga, Garima; Zafar, Noman
Introduction: Two valid group and saves are commonly required for patients undergoing laparoscopic appendicectomy and laparoscopic hernia repairs preoperatively; however, perioperative blood transfusions are seldom required. This is financially burdensome and frequently leads to delays in theatre lists. We performed a retrospective analysis to investigate blood transfusions performed perioperatively and within 28 days of these procedures. Method: We used our electronic records to collect data of all laparoscopic appendectomies and laparoscopic hernia repairs between March 2017 and March 2021. Patients of any age undergoing these operations were included. Patients requiring concomitant intra-abdominal surgery or who had incomplete medical records were excluded. Results: A total of 1891 patients were included, of which 1462 (77.3%) had a laparoscopic appendicectomy versus 429 (22.7%) who had a laparoscopic hernia repair. In all, 3507 group and saves were taken costing £47, 398.50. One patient (0.068%) required emergency blood transfusion (4 units of red cells) secondary to major haemorrhage. Conclusion: Our findings demonstrate that the incidence of perioperative blood transfusions for laparoscopic appendicectomy and laparoscopic hernia repairs is low, challenging the indication for routine preoperative group and saves.